(untitled) (Bangladesh Journal of Zoology, 2021)
The present study was designed to investigate Strongyloides stercoralis infection in rural communities of Savar and Gazipur. A total of 160 stool samples were collected from the inhabitants of the study areas during December 2016 to November 2017. The samples were processed by direct smear, formol-ether concentration technique and Harada-Mori culture. The overall prevalence of S. stercoralis was 10.63%; 11% in Savar and 10% in Gazipur. The elderly people were more prone to S. stercoralis infection. No respondent belonging to age group of 11-20 years was found positive for infection. Poor educational status, inferior financial condition and inadequate hygiene practice were found as potential risk factors (P<0.05). Noticeable prevalence was observed among the respondents living in mud floored house (13.46%), irregular nail clippers (22.73%), bare footers (14.89%) and laborers (27.27%) in Savar. Prevalence was high among the respondents deprived of institutional education (17.86%) in Gazipur. Bangladesh J. Zool. 48(2): 313-320, 2020